1988
DOI: 10.1063/1.454322
|View full text |Cite
|
Sign up to set email alerts
|

A multireference CI determination of the isotropic hyperfine constants for first row atoms B–F

Abstract: The requirements for obtaining converged isotropic hyperfine constants, Aiso, in first row elements B–F are investigated with extended basis set CI wave functions composed of single and double excitations from a multiconfiguration reference space. Since the restricted Hartree–Fock unpaired spin density at the nucleus is zero for these elements, correlation effects account for the entire answer. Although the wave functions computed in the present study uniformly recovered 94%–98% of the empirical correlation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Systematic studies of the basis set dependence of also for other systems such as I4N using MRSD-CI wave functions were reported by Engels et al [7] and Feller and Davidson [8]. For "F,, two theoretical studies are available: one by Nguyen and Ha [9] and the other by Carmichael [lo].…”
Section: Introductionmentioning
confidence: 97%
“…Systematic studies of the basis set dependence of also for other systems such as I4N using MRSD-CI wave functions were reported by Engels et al [7] and Feller and Davidson [8]. For "F,, two theoretical studies are available: one by Nguyen and Ha [9] and the other by Carmichael [lo].…”
Section: Introductionmentioning
confidence: 97%
“…The methods based on the complete active space selfconsistent field (CASSCF) and (uncontracted) multiconfiguration interaction (MRCI) methods have been reported as well. [13][14][15][16] Yet another approach is based on density functional theory (DFT). 10,[17][18][19][20][21] These approaches have been generalized to relativistic analogues to account for the scalar relativistic and spin-orbit effects.…”
Section: Introductionmentioning
confidence: 99%
“…For a nitrogen atom, which is a much simpler system with respect to spin density calculations than boron or carbon, 19,27 it was demonstrated that at least quadruple excitations are required if a single reference wave function is used. A multireference CI wave function based on a relatively small CASSCF reference function predicts a N spin density that is very close to FCI.…”
Section: Resultsmentioning
confidence: 99%